A variant space search method and its application to the optimization design of compressor profiles. Issue 9 (2nd September 2018) - Zhang, Jinhuan; Zhou, Zhenggui; Cao, Hui
ABSTRACT: Optimization methods have been widely used in practical engineering, with search efficiency and global search ability being the main evaluation criteria. In this article, the Bezier curve equivalent recursion is used in a genetic algorithm (GA) to realize the variant space search to improve the search efficiency and global search ability. The parameters related to this method are investigated by an optimization test of the simple curve approximation, which is then used for optimization designs of supersonic and transonic profiles. The results show that the GA can be improved if the variant space search method is added.